PENGARUH KEBIJAKAN PEMERINTAH PROVINSI RIAU DALAM MENINGKATKAN KUNJUNGAN WISATAWAN ASING KE RIAU TAHUN 2016 ( Studi Kasus: Wisatawan Negara Malaysia) - Artika, Mona Dwi; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This reseacrh aim to explain about the eefect of the effect of Riau Provincial Government policy in increasing the number of foreign tourist visits to Riau especially the Malaysian tourist. This research uses the qualitative descriptive as the method and secondary is the techniques of collection data. Futhermore author uses the globalism perspective with nation state as the level of analysis and uses the international cooperation and tourism concept.The Riau Provincial Government do some policy. The promotion through Riau Menyapa Dunia, infrastructure improvements,calendar of events, cerita baru center, city branding with Riau the Homeland of Melayu and the promotion to the annual agenda of Malaysia. The result of this research show that after Riau Provincial Govenrment did some policy in increasing the number of foreign tourist visits to Riau it has a positif effect. The effect of this policy is the improvement of economy in Riau Province like the increasing in foreign exchange from tourist sector amd the development of accommodation business. That policy also has an effect in increasing the number of foreign tourist visits to Riau especially Malaysian tourist. Key Words: Tourism, tourist, foreign exchange, policy, accommodation.